Vaginal Fold Histology Reduces the Variability Introduced by Vaginal Exfoliative Cytology in the Classification of Mouse Estrous Cycle Stages. (December 2014) - Gal, Arnon; Lin, Po-Ching; Barger, Anne M.; MacNeill, Amy L.; Ko, CheMyong
Vaginal exfoliative cytology is commonly used in biomedical and toxicological research to classify the stages of the rodent estrous cycle. However, mouse vaginal exfoliative cytology is commonly used as a stand-alone tool and has not been evaluated in reference to vaginal histology and serum sex hormone levels. In this study, the direct and Giemsa-stained methods of vaginal exfoliative cytology were compared in reference to vaginal fold histology and serum sex hormone levels. Both methods predicted the estrous stages similarly with mean discordance rates of 55%, 77%, 46%, and 31%, for diestrus, proestrus, estrus, and metestrus, respectively. From these results, we conclude that vaginal exfoliative cytology may be used as a general guide to determine the desired estrous stage end point and that a definitive confirmation of the estrous stage should be obtained from evaluation of vaginal fold histology. Confirmation of the stage of the estrous cycle by vaginal fold histology will decrease the variability otherwise introduced by misclassification of estrous cycle stages with vaginal exfoliative cytology.